Paroxysmal symptoms in multiple sclerosis. - Matthews, W B (1975)
The clinical features of paroxysmal symptoms occurring in 26 patients with multiple sclerosis are reviewed. The findings are considered to provide further support for the concept of lateral spread of axonal excitation within demyelinated plaques.